SAT0344 Treatment of Non-Infectious Aortitis: Study of 32 Patients from A Single Centre. (15th July 2016) - Fernández-Díaz, C.; Loricera, J.; Pena, C.; Blanco, R.; Hernández, J.L.; Carril, J.M.; Martínez-Rodríguez, I.; Canga, A.; Peirό, E.; Corrales, A.; Calvo-Río, V.; González-Vela, C.; et al.
Abstract : Background: Non-infectious aortitis is often an underrecognised condition. Early diagnosis and treatment is crucial to prevent serious complications. Corticosteroids represent the first-line therapy of non-infectious aortitis. However, disease-modifying antirheumatic drugs (DMARDS) and/or biologic therapy are usually required. Objectives: Our aim was to assess the treatment and outcome of patients diagnosed with non-infectious aortitis from a single centre. Methods: Retrospective study of 32 patients (22 women/10 men) diagnosed with non-infectious aortitis based on imaging techniques. We have considered 3 groups: group a) patients who only received corticosteroids; group b) patients treated with corticosteroids and DMARDs; and group c) those who required biologic therapy. Results were expressed as mean±standard deviation (SD) or as median and interquartile range (IQR) as appropriate. Wilcoxon test was used to compare the study parameters at baseline and at the last visit. Results: The mean age±SD of the patients was 68±11 years and the mean±SD follow-up was 24.7±22.7 months. Group a) included 11 patients; group b) 12 patients treated with methotrexate (MTX) and 2 hydroxychloroquine (in one of them associated to MTX); and group c) 9 patients on biologic therapy: adalimumab (ADA) (n=3), tocilizumab (TCZ) (n=5) and rituximab (RTX) (n=1). In this group, 8 patients were previously treated with DMARDS: MTX (n=7) and azathioprine (n=1). The results are shown in the TABLE . Two patients receiving MTX had to withdraw it due to raised liver function test, and two patients who were on TCZ had to discontinue it because of neutropenia. Moreover, one of them had angina pectoris related to a hypertensive episode during the third TCZ infusion. Conclusions: Corticosteroids are the cornerstone of treatment of noninfectious aortitis, although frequently DMARDS (usually MTX) and sometimes biologic therapy are required. The treatment seems effective and relatively safe. Acknowledgement: This study was supported by a grant from "Fondo de Investigaciones Sanitarias" PI12/00193 (Spain). This work was also partially supported by RETICS Programs, RD08/0075 (RIER) and RD12/0009/0013 from "Instituto de Salud Carlos III" (ISCIII) (Spain). Disclosure of Interest: None declared